LITERATURE REVIEW OF NEPHROTIC EDEMA MANAGEMENT: A Literature Review - Pramuti, Agysza Ulfiantika; Estu Pratiwi, Prasetyaning (Journal of Diverse Medical Research: Medicosphere, 2025)
Abstract Background. Nephrotic syndrome (NS) is a renal disorder characterized by proteinuria, hypoalbuminemia, hyperlipidemia, and edema. Among these, edema remains a prominent clinical manifestation affecting patient quality of life and signaling disease progression. Understanding its multifactorial pathophysiology is essential for optimizing treatment strategies. Methods. A systematic review of peer-reviewed literature from 2020 to 2024 was conducted using PubMed, ScienceDirect, and Elsevier. Search terms included "Edema," "Nephrotic Syndrome," "Proteinuria," and "Nephrotic Edema." Relevant articles, including case reports, reviews, and clinical studies, were critically analyzed to identify advances in understanding and managing edema in NS. Discussion. Edema in NS arises from a combination of hypoalbuminemia-induced oncotic pressure reductions, increased sodium retention, and altered vascular permeability. Standard therapies, such as diuretics and dietary sodium restriction, address these mechanisms but may be insufficient for resistant cases. Emerging strategies include combination diuretics, targeted immunomodulators, and personalized approaches based on genetic predispositions and hormonal influences. Advanced outcome measures now enable improved assessment of treatment effectiveness and patient outcomes experiences . Conclusion. Effective management of nephrotic edema requires a holistic approach, integrating conventional therapies with emerging innovations. Advances in molecular research and diagnostic precision are paving the way for personalized interventions, emphasizing the need for multidisciplinary care to improve outcomes and enhance patient quality of life.